Molecular Investigation of Geosmin and 2-Methylisoborneol Production by Some Species of Cyanobacteria - Mysoon M.AL-Taee; Fo'ad M. Alkam; Haider A. Alghanmi (Al-Qadisiyah Journal of Pure Science, 2018)
This study is considered the first of its kind in Iraq, It deals with compounds that never had been studied in Iraq called taste and odour compounds, mostfrequent were geosmin and 2-MIB. Two species were identified as producers for taste and odour compounds, the first was Phormidium retzii produced geosmin and Microcoleus vaginatus produced 2-MIB which were recorded for the first time in the world as a producer. The headspace solid phase microextraction (HS-SPME) method was used to extract these two compounds from aqueous solution, which were used for the first time in Iraq.The primers designed in this study for detection of genes responsible of geosmin production by Phormidium retzii and 2-MIB production by Microcoleus vaginatus when using genetic analysis by PCR technique which were geo1, geo2, geo3 and 2-MIB1, 2-MIB2, 2-MIB3 derived from cyanobacterial species exist online in National centre of biotechnology information (NCBI) site were discovered before which were producing geosmin and 2-MIB. The primers gave good consequences for detection the genes responsible of these two compounds. Thus, genetic analysis was considered one of the important method  and complementary for Instrumental Analysis (Chromatographic) for the detection of such compounds.